Differential Noradrenergic Modulation of Monetary Reward and Visual Erotic Stimulus Processing - Graf, Heiko; Wiegers, Maike; Metzger, Coraline D.; Walter, Martin; Abler, Birgit (Frontiers in Psychiatry, 2018)
We recently investigated the effects of the noradrenergic antidepressant reboxetine and the antipsychotic amisulpride compared to placebo on neural correlates of primary reinforcers by visual erotic stimulation in healthy subjects. Whereas amisulpride left subjective sexual functions and corresponding neural activations unimpaired, attenuated neural activations were observed under reboxetine within the nucleus accumbens (Nacc) along with diminished behavioural sexual functioning. However, a global dampening of the reward system under reboxetine seemed not intuitive considering the complementary role of the noradrenergic to the dopamine system in reward-related learning mediated by prediction error processing. We therefore investigated the sample of 17 healthy males in a mean age of 23.8 years again by functional magnetic resonance imaging (fMRI), to explore the noradrenergic effects on neural reward prediction error signalling. Participants took reboxetine (4mg/d), amisulpride (200mg/d) and placebo each for 7 days within a randomized, double-blind, within-subject cross-over design. During fMRI, we used an established monetary incentive task to assess neural reward expectation and prediction error signals within the bilateral Nacc using an independent anatomical mask for a region of interest (ROI) analysis. Activations within the same ROI were also assessed for the erotic picture paradigm. We confirmed our previous results from the whole brain analysis for the selected ROI by significant (p<0.05 FWE-corrected) attenuated activations within the Nacc during visual sexual stimulation under reboxetine compared to placebo. However, activations in the Nacc concerning prediction error processing and monetary reward expectation were unimpaired under reboxetine compared to placebo, along with unimpaired reaction times in the reward task. For both tasks, neural activations and behavioural processing were not altered by amisulpride compared to placebo. The observed attenuated neural activations within the Nacc during visual erotic stimulation along with unimpaired neural prediction error and monetary reward expectation processing provide evidence for a differential modulation of the neural reward system by the noradrenergic agent reboxetine depending on the presence of primary reinforcers such as erotic stimuli in contrast to secondary such as monetary rewards.